Peran Inovasi Program Satu Nagari Satu Event terhadap Pemberdayaan Ekonomi Lokal di Tanah Datar - Vanny, Dasti; Frinaldi, Aldri (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The One Nagari One Event Program (SESN) is a policy innovation by the Tanah Datar District Government in efforts to empower the local economy through the development of tourism and cultural potential. This study aims to analyze the role of program innovation in local economic empowerment in Tanah Datar. The research method uses a literature review by analyzing various relevant literature sources over a 3-month period. Data collection techniques were carried out through documentation studies and literature reviews, with data analysis using content analysis methods including categorization, synthesis, and interpretation. The results showed that the SESN program has had a positive impact on the local economy, marked by an increase in the number of events from 30 (2022) to 50 (2023), an increase in visitors from 85,100 to 167,850 people, and an increase in economic transactions from IDR 7.57 billion to IDR 9.035 billion. However, this program still faces challenges in terms of stakeholder coordination, limited human resources and budget, as well as the sustainability of economic impacts after the event. Continuous innovation in this program is needed to optimize local economic empowerment in Tanah Datar.